EXPERIENCES WITH APPLICATION OF PUBLIC PROCUREMENT IN BUS TRANSPORT IN THE UNITED KINGDOM - Poliak, Milos; Forrest, Linda; Semanova, Stefania (Doprava a spoje, 2012)
The paper deals with an application of Regulation (EC) No 1370/2007 that came into force on the 3rd of December, 2009. The aim of this regulation is to determine a procedure by which competent authorities (public sector buyers) may act in area of public passenger transport to ensure services of public interest. The aim of this procedure is to monitor achievement of greater volume of services, improve safety and increase quality of services at the lowest possible costs. The regulation sets out conditions which the public sector buyers must meet while ensuring of transport serviceability supported from public funds. Before the introduction of Regulation (EC) No 1370/2007 in 2009, most public sector buyers in Slovak Republic (SR) had signed contracts valid for ten years. This means that the regulation will be applied to public procurement in throughout SR from 2019. Due to previously mentioned facts, the objective of this paper is to describe experiences of application of Regulation (EC) No 1370/2007 in the United Kingdom, with reference to practical experiences of a particular bus carrier in Scotland.